A retrospective evaluation of blood cultures in a pediatric intensive care unit: a three year evaluation - Ergül, Ayşe Betül (Turk Pediatri Ars, 2017)
AIM: In this study, it was aimed to retrospectively assess the frequency and antibiotic resistance of microorganisms isolated from blood cultures of patients in a pediatric intensive care unit. MATERIAL AND METHODS: The study was conducted on blood culture tests obtained from patients in a pediatric intensive care unit and sent to a microbiology laboratory between 2013 and 2016. The species and antibiotic susceptibilities were assessed in microorganisms isolated from the blood cultures. RESULTS: Overall, 4239 blood cultures were obtained. Growth was detected in 324 blood cultures (7.6%). Of the microorganisms isolated, 195 (60.2%) were Gram-positive bacteria, and 107 (33.0%) were Gram-negative bacteria; 22 (6.8%) were fungi. The most commonly isolated microorganisms were Coagulase-negative staphylococci (45.1%), followed by Klebsiella pneumonia (14.5%), and Enterococcus faecalis (6.5%). Among the fungi, the most common was Candida albicans (59.1%), followed by Candida parapsilosis. The resistance rate against methicillin was 89.9% in coagulase-negative staphylococci, and 66% in S. aureus strains. The resistance rate against vancomycin was 3.6% in Enterococci spp. There was no resistance against linezolid in Gram-positive microorganisms. The rate of extended-spectrum beta lactamase positivity was found as 34% in Klebsiella spp. and 100% in Escherichia coli. The resistance rate against carbapenem was 44.9% in Gram-negative bacteriae. The resistance rate against carbapenem was 100% in Acinetobacter baumanii. In Candida albicans, resistance to amphotericine B was 61.5%, and resistance to voriconazole was 7.7%. CONCLUSIONS: To plan effective empiric antibiotic therapy against nosocomial infections in intensive care units, all units should have information about the characteristics of their own flora.